INVESTIGATING UNIVERSITY STUDENTS’ GREEN ENTREPRENEURIAL INTENTION: A PATHWAY TOWARDS GREEN ECONOMY - Prayogo, Jocelyn Cynara; ongkowijoyo, Gracia (PERFORMA, 2024)
Abstract: Environmental degradation is an urgency that all countries must overcome, and active participation is crucial for sustainable development. Indonesia is among the top ten contributors to global emissions, but green literacy is poorly known in developing countries. The Indonesian government has initiated to transform the economy towards green, sustainable, and circular. Small and medium-sized enterprises (SMEs) are fundamental pillars of Indonesia's economy, with entrepreneurs accounting for 61% of the overall value. Green entrepreneurs play a significant role in addressing environmental degradation and social issues while also facilitating the transition towards a sustainable green economy. Therefore, green entrepreneurs have a massive role in solving environmental damage and paving the path to green economic growth. Since youth represent the prospective entrepreneurs of the future, it is essential to foster their green entrepreneurship capabilities, to improve the economy's sustainability. This research adopted a quantitative methodology, wherein the data gathered through surveys was subjected to statistical analysis using the SmartPLS software. The present study employed the purposive non-probability sampling method to collect a sample of 235 Indonesian business management students as the objects. This study's findings suggest a positive and significant relationship between social responsibility, green cognition, and green entrepreneurial self-efficacy toward green entrepreneurial intention. In addition, the results show that green entrepreneurial self-efficacy partially mediates the relationship between social responsibility and green cognition variables toward students' green entrepreneurial intention. Previous study about entrepreneurship has been widely researched, however, green entrepreneurship is an emerging topic that has not been explored yet. The findings of this study show personality traits can influence students to engage in green entrepreneurship, respond to climate change, and contribute to a sustainable future. This research will provide valuable insights for policymakers and universities in designing effective strategies to foster individuals' green entrepreneurial traits. Suggestions for future research are also provided.